INTEGRATION OF LOCAL WISDOM VALU INTEGRATION OF LOCAL WISDOM VALUES IN LEARNING HISTORY THROUGH A CONTEXTUAL APPROACH AT SMA NEGERI 3 BALAESANG: Connecting Historical Learning with Local Cultural Values - Hidayat, Ulil; Takunas, Rusli; Nur, Rizka Fadliah (SOSIOEDUKASI, 2026)
This study aims to analyze the integration of local wisdom values in history learning through a contextual approach as an effort to overcome the tendency of history learning which is still textual, de-contextual, and able to internalize local cultural values. This research uses a qualitative approach with a case study design, with data collection techniques in the form of observation, in-depth interviews, and documentation, and is analyzed through the stages of data reduction, data presentation, and interactive verification. The results of the study show that the integration of local wisdom values is carried out through the contextualization of historical material with the socio-cultural reality of students, the use of the environment as a learning resource, and the application of participatory and dialogical learning methods. The contextual approach has been proven to be able to improve historical understanding, cultural awareness, and internalization of students' character values. This finding corroborates previous research that shows that learning based on local wisdom makes the learning process more meaningful, contextual, and relevant to students' experiences. Thus, the integration of local wisdom through a contextual approach is an effective, adaptive, and sustainable pedagogical strategy in the development of history learning that is oriented towards strengthening cultural character and identity.